Proceedings of the European Workshop on the Evaluation of Farm Investment Support, Investment Support for Improvement of Processing and Marketing of Agricultural Products - Angela Bergschmidt; Walter Dirksmeyer; Josef Efken; Bernhard Forstner; Inge Uetrecht (Bundesforschungsanstalt für Landwirtschaft (FAL), 2006)
Contents: i - Angela Bergschmidt, Walter Dirksmeyer and Bernhard Forstner - Proceedings of the European Evaluation Workshop – Foreword – PAPERS PRESENTED IN THE PLENARY SESSIONS – 3 - Stefan Meyer - Methods for the Evaluation of Investment Support – 15 - Andrea Pufahl - Programme Evaluation of Rural Development Plans – Purpose, Approaches and Exemplary Results – 27 - Carel Gosselink - Agri Finance: Lost without Support? – 33 - Anne Margarian - How to Evaluate a Measure without Goals – Considerations on the Basis of the Paradigmatic Example of Farm Investment Support in Germany – 45 - Rudy Ooijen - Ex Ante Evaluations of Rural Development Programmes – Not just an Appraisal – PAPERS PRESENTED IN THE SESSION ON FARM INVESTMENT SUPPORT – 61 - Angela Bergschmidt and Walter Dirksmeyer - A Comparison of Farm Investment Support in Selected EU Member States – 69 - Monika Beck and Thomas Dogot - The Use of Impact Indicators for the Evaluation of Farm Investment Support – A Case Study Based on the Rural Development Programme for Wallonia (2000 – 2006) – 79 - Barbara Costantini and Maria Cristina Sibilla - Implementation of Farm Investment Support in Italy – Mid-Term Analysis – 93 - Pawel Chmielinski - Regional Absorption Capacity of Farm Investment Support in Poland – 105 - Luis A. Collado Cueto - Effectiveness and Impacts of Farm Investment Support in Spain – The Experience of the Updated Mid-Term Evaluation (2000 – 2006) – 121 - Dimitros Lianos and Triantafyllia Giotopoulou - The Experience of the Evaluation of Farm Investment Support in Greece – 133 - Bernhard Forstner - Evaluation of Farm Investment Support in Germany – Lessons Learned from the Application of Different Approaches – 147 - Stephan Pfefferli - Impact Analysis of Investment Support for Agricultural Buildings in Switzerland – 159 - Justyna Ziólkowska, Joanna Nargiello and Cezary Klimkowski - The Analysis of Changes in Farm Investment Support Policy in Poland after Joining the European Union – PAPERS PRESENTED IN THE SESSION ON INVESTMENT SUPPORT FOR IMPROVEMENT OF PROCESSING AND MARKETING OF AGRICULTURAL PRODUCTS – 177 - Inge Uetrecht, Heinz Wendt, Volker Krah and Annette Trefflich - The Implementation of Investment Support for Improving Processing and Marketing of Agricultural Products in the EU Member States – An Overview – 187 -Andreas Pölking - Synthesis of the RDP Mid-Term Evaluation in Germany (16 Länder) and EC 15 in 2005 – Methodologies, Possibilities, Pitfalls and some Selected Results – 195 - Julia Neuwirth and Karlheinz Pistrich - Improving Processing and Marketing of Agricultural Products – Organisation, Problems and Results of Evaluation in Austria – 201 - Alois Grabner - Improving of Processing and Marketing of Agricultural Products – Assessment of Projects – 205 - Pedro Serrano - Support to Processing and Marketing of Agricultural Products in Portugal – 215 - Mark Temple - Two Approaches to Evaluation – The Case of the Processing and Marketing Grant in England – 227 - Jochen Nölle and Josef Efken - Does Complete Field Research Build a Good Basis to Evaluating the Measure? – CLOSURE OF THE EUROPEAN EVALUATION WORKSHOP – 241 - Bernhard Forstner and Heinz Wendt - Summary and Final Discussion
urn:nbn:de:gbv:253-200909-zi040499-2
Keywords: 330; Agrarpolitik; Investitionspolitik; Landwirtschaft; Wirkungsanalyse; Deutschland; Belgien; Italien; Polen; Spanien; Griechenland; Schweiz; Österreich; Großbritannien; EU-Staaten